1981
DOI: 10.1159/000198543
|View full text |Cite
|
Sign up to set email alerts
|

Antinuclear and Pancreatic Acinar Cell Antibodies in Pancreatic Diseases

Abstract: Recently, the presence of acinar cell antibodies (ACA) and antinuclear antibodies (ANA) in acute and/or chronic pancreatitis have been discussed in the light of an immunological pathogenesis of pancreatitis. In the present study sera of 109 patients with pancreatic diseases were scanned for ACA and ANA which were found in 5 and 16 patients, respectively. The frequency of ACA and ANA was similar in patients with pancreatitis of known and unknown aetiology. In conclusion, the presence of ACA and ANA seems to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
1

Year Published

1983
1983
2003
2003

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
1
18
1
Order By: Relevance
“…1 Since Sarles et al 2 observed a case of pancreatitis associated with hypergammaglobulinemia, the occasional coexistence of pancreatitis with other autoimmune diseases, such as Sjögren's syndrome (SjS), 3 primary sclerosing cholangitis (PSC), 4,5 and primary biliary cirrhosis (PBC) 4 has been reported. These findings support the hypothesis that an autoimmune mechanism may be involved in the pathogenesis and pathophysiology of pancreatitis in some patients, [6][7][8][9][10][11][12][13][14][15][16] which leads us to the concept of an autoimmune-related pancreatitis (AIP), 15 the so-called "autoimmune pancreatitis." 8 Although it has not been widely accepted as a new clinical entity, the present review discusses the recent concept of AIP from the clinical and animal experimental aspects.…”
Section: Introductionsupporting
confidence: 77%
“…1 Since Sarles et al 2 observed a case of pancreatitis associated with hypergammaglobulinemia, the occasional coexistence of pancreatitis with other autoimmune diseases, such as Sjögren's syndrome (SjS), 3 primary sclerosing cholangitis (PSC), 4,5 and primary biliary cirrhosis (PBC) 4 has been reported. These findings support the hypothesis that an autoimmune mechanism may be involved in the pathogenesis and pathophysiology of pancreatitis in some patients, [6][7][8][9][10][11][12][13][14][15][16] which leads us to the concept of an autoimmune-related pancreatitis (AIP), 15 the so-called "autoimmune pancreatitis." 8 Although it has not been widely accepted as a new clinical entity, the present review discusses the recent concept of AIP from the clinical and animal experimental aspects.…”
Section: Introductionsupporting
confidence: 77%
“…Our results, unlike those reported by oth ers [5], showed a high number of positive sera for AA in CP. This discrepancy could be explained by the higher number of different AA that were checked in our series of pa tients.…”
Section: Discussioncontrasting
confidence: 99%
“…There are scanty and conflicting reports about the presence of AA in sera of patients with a well-documented CP [4,5], In our study AA were found with the same frequence in CP as well as in LC. in which AA have been commonly described [10][11][12], In both the dis eases we observed a significant occurrence of AA compared to healthy subjects.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…1 A proportion of cases labeled "idiopathic" probably represent autoimmune-mediated disease. [2][3][4] Sarles et al 5,6 first reported cases of pancreatitis associated with hypergammaglobulinemia. The concept of autoimmune-related pancreatitis (AIP) was originally proposed by Yoshida et al 7 and reviewed by Okazaki et al 8 and Okazaki and Chiba; 9 and the following characteristics have been described: [7][8][9][10][11][12][13] (1) diffuse enlargement of the pancreas and irregular narrowing of the main pancreatic duct (MPD); (2) increased levels of serum immunoglobulin G (IgG) and the presence of some autoantibodies; (3) asymptomatic or minimal symptoms, such as epigastralgia or back pain, compared to ordinary alcoholic chronic pancreatitis; (4) histologically, fibrotic changes with lymphocyte infiltration around the pancreatic ducts; and (5) good response to steroid therapy.…”
Section: Introductionmentioning
confidence: 99%